Social problems and social control: the case of abortion - Burns, Stacy Lee (Democracy, governance, and law, 2025)
Purpose - This chapter articulates a theoretical framework of institutional constructionism for analyzing the social problem of abortion and focuses on the development and operation of social control institutions in response. Methodology/approach - The study provides an overview of the historical and current trends in judicial and legislative actions leading to and following the landmark Roe v. Wade decision. We support our argument with data drawn from case law, statutes, popular initiatives, and policy analysis. Findings - The chapter documents three stages in the development of social control of abortion, which include criminalization, establishment of a right to abortion, and overturning of that right. The analysis is longitudinal and traces how earlier developments in law, politics, and culture become historical contingencies that affect later events and later developments modify earlier events related to abortion. The study finds that when the Supreme Court disregards precedent, it comes under enhanced public scrutiny and undermines its institutional legitimacy. Originality/value - Our institutional perspective differs from earlier frameworks for analyzing social problem construction in that it does not specify a pre-determined course of institutional development but emphasizes the contingencies driving transitions in the developmental trajectory of social control of abortion. The chapter is timely and provocative as it deals with major changes in the rights of women to control their own bodies initiated by the recent Supreme Court decision in Dobbs v. Jackson Women’s Health Organization which has resulted in a flurry of state and federal judicial actions, dismantling one social control structure, and building another.